PI Controller Untuk Mengatur Kecepatan Motor Induksi 1 Fasa - Siti Nur Alima; Mila Fauziyah; Denda Dewatama (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
Induction motors are widely used in the industrial world, home-based businesses as well as in households. Currently in the process of making tofu an induction motor is used as a motor to drive soy blending blades. At this time the use of induction motors is still manually by requiring the operator to regulate the speed of the motor. To reduce operator work, it is necessary to apply PI control as a motor speed controller so that a constant motor rotation is obtained. 1 phase induction motor can be adjusted with variable speed drive (VSD) 0.75KW 1 phase. Blending blade drive uses 0.5HP 1 phase induction motor. In the application of PI control requires some hardware namely Arduino Uno as a minimum system that gives PWM circuit input commands. And the speed sensor as a motor blending speed reader. PI tuning values obtained from the application of the Ziegerl-Nichols I method with the best Kp and Ki tuning values are 1.35 and 0.02673. This research was conducted with 3 speed variables namely 1400 rpm, 1300 and 1200 rpm. From the application of Kp and Ki tuning values, the smallest error value is 4.08% at 1400 rpm with the system response time peak (tp) 5s, rise time (tr) 3s faster, delay time (td) 3s, and settling time (ts) 9s , and a maximum overshoot of 9.8%.